2019
DOI: 10.1103/physrevb.99.165305
|View full text |Cite
|
Sign up to set email alerts
|

High-fidelity optical quantum gates based on type-II double quantum dots in a nanowire

Abstract: We propose an optical gating scheme for quantum computing based on crystal-phase type II double quantum dots in an InP nanowire. The qubit is encoded on the electron spin and the gate operations are performed using stimulated Raman adiabatic passage (STIRAP), using the orbital degree of freedom in double quantum dots to form an auxiliary ground state. Successful STIRAP gating processes require an efficient coupling of both qubit ground states of the double quantum dot to the gating auxiliary ground state, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Control of such structures at the ML level is actually necessary for promising applications. [44][45][46] Note that if group V sidewall diffusion contributed to droplet refill, [35] this would only require stems longer than the corresponding diffusion length, in addition to constant NW and droplet radii. [36,47] We showed that the reason for this quasideterministic growth regime is the compensation between the propagation time and preceding waiting time, expected to occur when there is never enough group V atoms in the catalyst particle to produce a full ML at nucleation.…”
Section: Discussionmentioning
confidence: 99%
“…Control of such structures at the ML level is actually necessary for promising applications. [44][45][46] Note that if group V sidewall diffusion contributed to droplet refill, [35] this would only require stems longer than the corresponding diffusion length, in addition to constant NW and droplet radii. [36,47] We showed that the reason for this quasideterministic growth regime is the compensation between the propagation time and preceding waiting time, expected to occur when there is never enough group V atoms in the catalyst particle to produce a full ML at nucleation.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction amplitude depends on the atomic quantum number, and in addition for the Förster resonances the interaction strength tuned by an applied electric field provides a great control flexibility [7,22,23,35]. Similar interactions occur also in artificial atoms, as the ground state interactions in double quantum dots in a nanowire [40].…”
Section: Introductionmentioning
confidence: 95%
“…In our previous work 18 , we have shown that GaAs QDs can be embedded in AlGaAs nanowires during bottom-up growth in a molecular beam epitaxy reactor, adding new possibilities to the system. For instance, any number of emitters can be precisely positioned within the same nanowire, making the nanowire QDs structure an ideal platform for advanced multi-qubit devices 19,20 that are not possible today with their bulk counterparts. Also, the precise size and position of each emitter can be controlled during growth, enabling tuning of the emission wavelength and fabrication of complex devices.…”
Section: Introductionmentioning
confidence: 99%